2019
DOI: 10.1016/j.toxlet.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioassay investigations of suspected obesogen monosodium glutamate at the level of nuclear receptor binding and steroidogenesis

Abstract: Highlights  Monosodium glutamate (MSG) is a suspected obesogen.  There is a link between exposure to MSG and alterations in steroid hormone levels.  MSG can antagonise the androgen receptor in a dose dependent manner.  The androgen receptor plays an important role in regulating metabolic homeostasis and is an emerging target for diabetes and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Animal models have the distinct and obvious disadvantage of not accurately replicating human physiology. However, animal models are an important and widely Bisphenol A (BPA) [97][98][99] Bisphenol S (BPS) [102] Bisphenol A diglycidyl ether (BADGE) [100] Triphenyltin [95] Dioctyl sodium sulfosuccinate (DOSS) [52] Geneistein & naringenin [103] Phthalate monoesters [32] 4-nonylphenol (NP) [101] Mono-ethylhexyl phthalate (MEHP) [50] Flavanone [104] Bixin, norbixin [105] Emodin [106] C2C12 (murine) Mono-ethylhexyl phthalate (MEHP) [50] HELA (human) Mono-ethylhexyl phthalate (MEHP) [50] Human embryonic kidney cells (HEK293C) Dioctyl sodium sulfosuccinate (DOSS) [52] HepG2 (human liver carcinoma cells) Bisphenol A (BPA), Bisphenol S (BPS) [102] Human adipose-derived stem cells (hASCs) Bisphenol A (BPA), Bisphenol A diglycidyl ether (BADGE) [102] Tributyltin (TBT) [44] Murine adipose derived stem cells (mASCs) Bisphenol A (BPA), Bisphenol A diglycidyl ether (BADGE) [102] Tributyltin (TBT) [44] Fao (murine hepatoma cells) Phthalate monoesters [32] COS (monkey kidney-derived cells) Bisphenol A (BPA), Bisphenol A diglycidyl ether (BADGE) [102] MBzP, MBuP [50] Mono-ethylhexyl phthalate (MEHP) [50,107] THP-1 macrophages (human) Psi-baptigenin, hesperidin [108] TARM-Luc (human, transfected T47-D epithelial cells) Monosodium glutamate (MSG) [109] KS483 (murine calvaria) Soy phytoestrogen genistein [110] C57BL/6 (murine-derived bone marrow stromal cells) Firemaster 550 [51] collagen embedded silk scaffolds Human embryonic-derived stem cells (hESCs) Tributyltin (TBT), Bisphenol A (BPA), Bisphenol S (BPS) [111] silk scaffolds Human adipose-derived stem cells (hASCs), Human umbilical vein endothelial cells (HUVECs)…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…Animal models have the distinct and obvious disadvantage of not accurately replicating human physiology. However, animal models are an important and widely Bisphenol A (BPA) [97][98][99] Bisphenol S (BPS) [102] Bisphenol A diglycidyl ether (BADGE) [100] Triphenyltin [95] Dioctyl sodium sulfosuccinate (DOSS) [52] Geneistein & naringenin [103] Phthalate monoesters [32] 4-nonylphenol (NP) [101] Mono-ethylhexyl phthalate (MEHP) [50] Flavanone [104] Bixin, norbixin [105] Emodin [106] C2C12 (murine) Mono-ethylhexyl phthalate (MEHP) [50] HELA (human) Mono-ethylhexyl phthalate (MEHP) [50] Human embryonic kidney cells (HEK293C) Dioctyl sodium sulfosuccinate (DOSS) [52] HepG2 (human liver carcinoma cells) Bisphenol A (BPA), Bisphenol S (BPS) [102] Human adipose-derived stem cells (hASCs) Bisphenol A (BPA), Bisphenol A diglycidyl ether (BADGE) [102] Tributyltin (TBT) [44] Murine adipose derived stem cells (mASCs) Bisphenol A (BPA), Bisphenol A diglycidyl ether (BADGE) [102] Tributyltin (TBT) [44] Fao (murine hepatoma cells) Phthalate monoesters [32] COS (monkey kidney-derived cells) Bisphenol A (BPA), Bisphenol A diglycidyl ether (BADGE) [102] MBzP, MBuP [50] Mono-ethylhexyl phthalate (MEHP) [50,107] THP-1 macrophages (human) Psi-baptigenin, hesperidin [108] TARM-Luc (human, transfected T47-D epithelial cells) Monosodium glutamate (MSG) [109] KS483 (murine calvaria) Soy phytoestrogen genistein [110] C57BL/6 (murine-derived bone marrow stromal cells) Firemaster 550 [51] collagen embedded silk scaffolds Human embryonic-derived stem cells (hESCs) Tributyltin (TBT), Bisphenol A (BPA), Bisphenol S (BPS) [111] silk scaffolds Human adipose-derived stem cells (hASCs), Human umbilical vein endothelial cells (HUVECs)…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…Although no studies have shown direct binding of glutamate ligand to steroid receptors, a few studies have suggested indirect interactions. First, in hippocampal neurons, androgen receptor activation changed how glutamate affected the intracellular calcium response (Foradori et al, 2007) and that glutamate had antagonistic effects on androgen receptor (Shannon et al, 2019). Furthermore, glutamate decarboxylase 65 converts glutamate to GABA, and it regulated androgen receptor binding to nuclear proteins in the context of prostate cancer (Gao et al, 2019).…”
Section: Potential Role Of Glutamate In Steroid-independent Female Sementioning
confidence: 99%
“…Formazan crystals were solubilised in DMSO facilitated by agitation at 37 °C. Optical density was measured, as previously described (Shannon et al 2019), using a Sunrise spectrophotometer at 570 nm with a reference filter at 630 nm (TECAN, Switzerland). Metabolic activity was calculated as a percentage absorbance of the sample compared with the absorbance of the SC.…”
Section: Mtt Assaymentioning
confidence: 99%